The strength-ductility balance of Al0·4CoCu0.6NiTix (x≤1.0) and Al0·4CoCu0·6NiSi0.2Tix (x≤0.5) high entropy alloys by regulating the proportion of Ti and improving the cooling rate. (September 2018) - Chen, Yongxing; Zhu, Sheng; Wang, Xiaoming; Yang, Baijun; Ren, Zhiqiang; Han, Guofeng; Wen, Shu
Abstract: The work prepared Al0·4 CoCu0·6 Ni(Si0.2 )Tix (Si0 Tix (x ≤ 1.0) and Si0.2 Tix (x ≤ 0.5)) high entropy alloys (HEAs) with high strength and excellent plasticity by optimizing the added ratio of Ti and rapid cooling, discussed the effects of Ti and cooling rate on HEAs' microstructures and mechanical properties. The results showed that arc melted and copper injected Si0 Tix HEAs' phase structures changed gradually from "fcc + L12 (Si0 Ti0.25 )" to "fcc + L12 +minor bcc (Si0 Ti0.5 )" and finally to "fcc + L12 +bcc + Ni3 Ti-type phase (Si0 Ti0.75, Si0 Ti1.0 )". But they transformed from "fcc + L12 +bcc + Ni16 Ti6 Si7 -type phase (Si0·2 Ti0.25 )" to "fcc + L12 +bcc + AlNi2 Ti-type + Ni16 Ti6 Si7 -type phase (Si0·2 Ti0.5 )" for Si0.2 Tix HEAs. The micro-hardness of arc melted and copper injected HEAs gradually increased compared with Si0 Ti0 matrix HEA and that of copper injected HEAs were larger than arc melted HEAs (except Si0 Ti0.5 ). The compressive properties of Si0 Ti0.25, Si0 Ti0.5 and Si0·2 Ti0.25 HEAs were relatively better, in which, the yield strengths of copper injected Si0 Ti0.25, Si0 Ti0.5 and Si0·2 Ti0.25 HEAs were 2.7, 2.9 and 4.8 times than that of arc melted Si0 Ti0 matrix HEA (295 MPa), the fracture strain rates of the corresponding HEAs were 47.1%, 22.4% and 13.5% respectively. It introduced three strengthening mechanisms of solid solution strengthening, trace phase transformation and fine grain strengthening and realized HEAs' strength-ductility balance. Highlights: Arc melted and copper injected Al0·4 CoCu0.6 NiTix and Al0·4 CoCu0·6 NiSi0.2 Tix HEAs were prepared. The optimal proportion of Ti was verified to be less than 14.29% for Al0·4 CoCu0.6 NiTix and 7.25% for Al0·4 CoCu0·6 NiSi0.2 Tix . Phase transformation, solid solution and fine grain strengthening were introduced. Realize HEAs' strength-ductility balance.